Study of the Comorbidity Between Cases of Acute Peripheral Vestibulopathies and COVID-19. Issue 8 (7th September 2021) - Charpiot, Anne; Hautefort, Charlotte; Jourdaine, Clément; Lavieille, Jean-Pierre; Levy, Daniel; Poillon, Guillaume; Tighilet, Brahim; Weckel, Alexandra; Chabbert, Christian
Abstract : Importance: An infective etiology of acute peripheral vestibulopathy (APV) has long been hypothesized. In the context of coronavirus disease 2019 (COVID-19), we examined the possible comorbidity between these two entities. Objectives: APV is the second most common cause of vestibular disorders and results from a sudden and unilateral loss of vestibular inputs. The characteristic signs and symptoms include sudden and prolonged vertigo, absence of auditory symptoms, and absence of other neurological symptoms. An infective etiology of APV has long been hypothesized on the basis of its association with respiratory tract infections and its frequent occurrence in epidemics. Possible comorbidity with herpes simplex virus type 1 reactivation or influenza virus infection has also been proposed. This study was designed to assess the possible comorbidity between APV and COVID-19. Design/setting/participants: Quantification of the number of hospital admissions for APV over the period from February to May 2020 was carried out in 5 French hospitals. A comparison with 2018 and 2019 entries over the same period was made. Comorbidity between APV and COVID-19 infection was investigated. Results: No significant increase in admission for APV was noticed over the examination period. No significant difference was noticed among hospitals located in COVID-19 high- and low-risk zones for SARS-CoV-2. No significant increase in the severity of the APV cases was noticed. No case of comorbidity between APV and SARS-CoV-2 infection was reported. Based on our observations, no correlation was made between APV and COVID-19. Conclusion: Based on our observations, COVID-19 is not statistically correlated with APV.